PENGARUH CORPORATE REPUTATION TERHADAP FINANCIAL PERFORMANCE MELALUI INNOVATION CAPABILITY SEBAGAI INTERVENING VARIABLE PADA INDUSTRI PERHOTELAN DI SURABAYA - Ni Gusti Ayu Putu Sueka Putri (Business Accounting Review, 2016)
This study aimed to examine the direct and significant effect of corporate reputation to innovation capability; innovation capability to financial performance; and corporate reputation to financial performance in hospitality industry in Surabaya. This study also examine the indirect and significant relationship of corporate reputation to financial performance through innovation capability as intervening variable in hospitality industry in Surabaya. This study used a quantitative approach, and the data were obtained through distributing questionnaires to hospitalities industry in Surabaya and processed by using smartPLS software. This study showed that there was a positive and significant relationship of corporate reputation to innovation capability; innovation capability to financial performance; and corporate reputation to financial performance in hospitality industry in Surabaya. But, innovation capability was inadequate to be an intervening variable between corporate reputation and financial performance because the direct relationship between corporate reputation and financial performance gave greater effect than if it was through innovation capability.